Teaching Methods Used by Teachers in Primary Schools Inclusive - Veronika, Veronika (Edumaspul: Jurnal Pendidikan, 2019)
This study aims that all children with special needs get the same rights to receive equal education in class together with their age friends. This research is a descriptive study, which seeks to describe the events that exist in the world of education, especially in terms of channeling knowledge to students. The type of research used in this study is qualitative research. The techniques used in collecting data are interview techniques and direct observation in schools. Education and diversity cannot be separated, what needs to be known is how education is able to unite differences by providing good educational equality. Good for normal children and those with special needs. The purpose of education is to encourage good change, both for individuals, groups and even groups. Inclusive education is child-friendly education, which means that from every system that services are provided to students who have learning disabilities or special needs to learn in ordinary class schools along with their friends.